Efficience of repetibility methods in final stages of the sugarcane genetic breeding (Research, Society and Development, 2020)
The objective this work was to verifield efficience of repetibility methods in the genotypes sugarcane selection on final stages of experimentation. The experiment was conducted in randomized block design with four repetitions. Were evaluated sixteen genotypes in four harvest cycles. The caracters analyzed were POL tonnage per hectare, sugarcane tonnage per hectare and total recoverable sugar tonnage per hectare. Were used four methodologies for repetibility analyses: variance analyse, principal components, estructural analyse and mixed linears models. The genotypes RB96972616 and RB972631 showed hight productivity, hight genetics valours predicteds and showed high genetic means free from interactions. By the variance analyse methods, of the principal components and estructural analyse three assessments would be necessary to select genotypes with 80% of predictability of the your real valours. The mixed models methodology, showed more efficient because besides to identified genotypes with genotipic stability in the harvest cycles, revealed that, through a 90% accuracy, two evaluations are enough to selected genotypes with high regrowth capacity, in the final stages of experimentation.